The Synthesis and Preliminary Anticancer Evaluation of 6-Mercaptopurine -Methotrexate Conjugate as Possible Mutual Prodrug - Asmaa Safwan Al-darraji; Mohamed H.Mohamed (College of Pharmacy University of Baghdad, 2019)
Small molecules drug conjugate mutual prodrug design  (SMDC) composed of folate &lethal agent conjugate  , rigidly bonded via hydrophilic bridge& self immolative disulfide  bond   ;  represent new interesting approaches for cancer treatment , the component of SMDC intended to be as possible suit targeted folate receptor , along with greater conservation  of component until reaching targeting tumor tissue . The  designing & synthesis of compound VI & IIX derived from 6-MP & MTX conjugate altogether as mutual prodrug were  processed forward  successfully by multiple steps procedure , and by TLC  spectrophotometry preliminary analysis assess in detection of  products & their intermediate , along with their purity . The structure of two final compounds & their intermediate were proclaimed by melting point measurement , infrared spectrometry & HNMR analysis given results greatly correspond with theoretical proposed chemical structure of synthesized compounds . Furthermore anticancer evaluation on cell line level had been done for two  final compound against MCF-7& SKO-3 types of cancer cell & the result were confirmed which show greater cytotoxic  tumor activity of two final compound ,while compound IIX  possess optimal activity proportional with increase number of 6-MP residue .